FAKTOR - FAKTOR PENENTU KEPUTUSAN PETANI SAWAH KE PERIKANAN DI DESA LIMAN SARI BUAY MADANG TIMUR KABUPATEN OKU TIMUR - Sudarti (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2015)
The purpose of this research were to : (1) Analyze the factors that influence farmers to transfer rice paddy fields to fishing commodities, (2) Counts how differences in income received by households of farmers of paddy rice over to fishery commodities. This research was conducted in the village of Sari Liman Eastern District of Buay Madang East Ulu Ogan Ogan. The location determination is done intentionally (purposive), from 28 villages in the District Buay Madang East only village Liman Sari selected researchers to conduct research on over commodity rice paddy fields to fishing with the consideration that the village catfish production of the highest and the land area widest among other villages. Collecting data on the location of the research conducted in March and June 2013. The study found that the factors that influence household decisions to transfer commodity farmers in rice paddy fields to fishing at test level to 20%, ie farmers' income (4.3%), the number of production (12.9%) and the risk of farming (12.6%), while the area of land owned no real effect, and the results of statistical analysis using Wilcoxon sign test analysis, the obtained value Zhitung = -5.373 <Ztabel with p value (Asymp sign 2 tailed) = 0.000 which is less than the critical value of 0.05 research. This indicates that the income of farmers who perform over paddy rice commodity to larger catfish farming is Rp 94,833,642, - per year per hectare than rice paddy farming income that does not do over the function of the land is Rp 25,154,791, - per year per hectares.